Technical countermeasures for deep pumping of highly deviated wells in deep reservoir - ZHANG Jin,TIAN Hongbo,HU Yuxin (Youqicang pingjia yu kaifa)
Nanpu Oilfield is located in the tidal sea with limited oil well spacing, and the overall development is dominated by highly oblique directional wells. Due to the characteristics of reservoir formation, the fault blocks are developed and broken, and the transverse area is small, the longitudinal layer distribution is large, and there are many oil wells with insufficient liquid supply in the low energy area. The conventional pump running depth is difficult to meet the supply and drainage requirements of continuous production, resulting in low efficiency of a single well. At the same time, the dissatisfaction of the pump barrel aggravates the complexity and eccentric wear degree of the down-hole rod stress. Based on the comprehensive evaluation of the rod, pipe and pump of the pumping unit system, the technical countermeasures of deep pumping are put forward. And the stimulation potential of deep pumping amplified pressure difference is predicted by the reservoir pressure and production parameters. The stress calculation after multi-stage rod deepening and the extension of production cycle are studied. After the simulation of the stress change of the rod column after deep pumping by the software, the stress test and theoretical calculation of the rod column at different depths after deep pumping are compared, and the related supporting technology is optimized to ensure the stress safety of the rod column after deep pumping. After deep pumping, the oil well dynamic fluid level decreased and the productivity increased. The increase of subduction reduced the filling dissatisfaction of the pump barrel. The setting depth of the pump is deepened averagely by 800 meters and can reach a depth of 3 300 meters. The production pressure difference, the pump efficiency, and the single well oil increment increase by 6 MPa, ten percentage points and 300 tons respectively on average. At the same time, the effect analysis and experience summary are carried out for oil wells with different reservoir properties and different liquid supply capacity, and the feasibility evaluation method of deep pumping in different oil wells is formed.